Silencing the opposition : how the U.S. government suppressed freedom of expression during major crises - Smith, Craig R. (Albany : State University of New York Press, 2011)
Annotation This title examines major challenges to the First Amendment and focuses on the extremely important paradigm shift of freedom of expression in the post-9/11 era.
Machine generated contents note: ch. 1 Alien and Sedition Crisis / Craig R. Smith -- ch. 2 Lincoln and Habeas Corpus / Stephanie J. Hurst -- ch. 3 Radical Republicans / Craig R. Smith -- ch. 4 Suppression of Native American Culture / Stephanie J. Hurst -- ch. 5 Silencing the Union Movement / Andrew Sachs -- ch. 6 Suppression of the Suffrage Movement / Amy L. Heyse -- ch. 7 Red Scares / Craig R. Smith -- ch. 8 Suppression During the Vietnam Era / Karen Rasmussen -- ch. 9 Suppressing Political Speech Through Broadcast Regulation and Campaign Reform / Craig R. Smith -- ch. 10 9/11 and the Ensuing Restrictions on Civil Liberties / R. Brandon Anderson -- ch. 11 Conclusion / Craig R Smith.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Freedom of speech -- United States -- History; Political oratory -- United States -- History; Liberté d'expression -- États-Unis -- Histoire; Éloquence politique -- États-Unis -- Histoire; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Freedom of speech; Political oratory; United States; History